Croce, Gentile and Gramsci on Translation - Jervolino, Domenico (International Gramsci Journal, 2023)
The activity of translating is as old as the entire history of human civilization. Yet, according to some, it is only in the second half of the twentieth century that translation became the subject of a specific discipline, or, more correctly, that it became the subject of a broad field of interdisciplinary studies, from linguistics to semantics, from literary criticism to comparative literature, and, more recently, even philosophy itself. This is so to the extent that the first scholars of translation in France have even spoken of a tournant philosophique de la traduction [philosophical turn of translation].1 It is natural to look back and attempt to delineate a history of the ideas about translation elaborated in the remote and in the near past once the theme of translation has imposed itself in various ways in the arena of contemporary culture, and therefore to find important precursors and ancestors, even though their contribution was limited often either to fragments or to opinions expressed in the margins of works devoted to other subjects or to comments about their translations.